Active Expression of Retroelements in Neurons Differentiated from Adult Hippocampal Neural Stem Cells - Antoszczyk, Slawomir; Terashima, Kazuyuki; Warashina, Masaki; Kuwabara, Makoto Asashima and Tomoko (IntechOpen, 2012)
None